Influences of the Circular Economy on The Companies' Financial Performance in The Food Industry - Ioana-Cristina TIMOFEI; Lidia VESA; Claudia Diana SABAU-POPA; Marcel Ioan BOLOS (Communications of International Proceedings, 2022)
In the past years, the circular economy concept and its influences has gained increasing attention worldwide. Together with the international organizations and governments, the companies have begun to embark on circular economy initiatives. The goal of this research paper is set to ascertain the relationship between circular economy and financial performance of companies from the food industry of Romania, based on an analysis of the data covering the years 2016 to 2021. The hypotheses were tested using Eviews software for panel data analysis, resulting three regression models used to study the correlation between selected variables. The dependent variables are positively associated with Exports: Residues & Waste and negatively associated with Imports: Residues & Waste. But, considering the Prob (F-statistic), it can be concluded that, at the level of the total population, only the variable Net Income/Net Sales is influenced by the both indicators of the circular economy, and in the case of Return on Assets, only by Imports: Residues & Waste. If the Imports: Residues & Waste Rate increased by 1%, Net Income/Net sales would decrease by 0.48%, and Return on Asset would decrease by 0.12%. In the case of Exports: Residues & Waste Rate, an increase by 1%, Net Income/Net sales would increase by 0.22%. The results of the study support the idea of a low degree of implementation of the circular economy in Romania. Building a circular economy is a complex and long-term process, and Romania is still at the beginning.
Keywords: Circular economy; Food industry; Residues & Waste; Net sales Growth Rate; Net Income; Return on Assets